Larval development and osteology of Callanthias platei (Teleostei: Callanthiidae) from Desventuradas Islands, South Pacific - Zavala-Muñoz, Francisca; Bustos, Claudia A.; Landaeta, Mauricio F.; Konstantinidis, Peter (Zootaxa, 2020)
Larvae of the Juan Fernández Splendid Perch, Callanthias platei Steindachner, 1898 (Teleostei: Callanthiidae), are described for the first time. The five available specimens, ranging from 3 mm notochord length (NL) to 6.1 mm standard length (SL), were collected with plankton nets near Desventuradas Islands, Southeast Pacific, during the austral spring of 2015 and 2016. The larvae are deep bodied with a narrow caudal peduncle, a large head and a triangular, coiled gut. The pigmentation is scarce in preflexion larvae but increases after flexion. All individuals have several groups of head spines: anterior and posterior preopercular, interopercular, subopercular, opercular and supracleithral. The formation of all fins occurs early in development, with the pectoral fins appearing first and the pelvic fins last. The osteological development of the skull, vertebral column, fins, and scales are described.